Aspects of Ecological Justice in The Arrangement of Pelaba Pura Land in Bali - Nyoman Satria Perwira, I; Gusti Ayu Ketut Rachmi Handayani, I; Karjoko, Lego (International Journal of Educational Research & Social Sciences, 2023)
Indigenous peoples in Bali arrange life in such a way as to create harmony, one of the things that are regulated is the Pelaba Pura land which is used for ceremonial and gardening places, but in its application there are still many conflicts between the village and the community itself due to positive laws that have not regulated much about the Pelaba Pura Land. The purpose of the study was to understand the land arrangement of Pelaba Pura and its expediency and whether it was based on ecological justice. The research carried out is doctrinal research with a statutory approach using primary materials and anconceptualcept approach. This research uses deductive and inter-achievement syllogism analysis techniques on various primary legal materials in the form of laws and regulations, including Law Number 5 of 1960 concerning Agrarian Principles, Law No.38 of 1963 concerning the Appointment of Legal Entities that have Land Rights, and Law no.32 of 2009 concerning Environmental Protection and Management. The results of the study found that the management of the Pelaba Pura land in Bali is still not in line with the Palemahan concept, namely between humans and nature because not paying attention to the environmwhileises the loss of the actual benefit of Pelaba Pura and the Temple Collector is not so good at carrying out its obligations to maintain the function of the Pelaba Pura Land.